Estrogen withdrawal alters cytoskeletal and primary ciliary dynamics resulting in increased Hedgehog and osteoclastogenic paracrine signalling in osteocytes. - Hoey, David (My University, 2021)
Estrogen deficiency during post-menopausal osteoporosis leads to osteoclastogenesis and bone loss. Increased pro-osteoclastogenic signalling (RANKL/OPG) by osteocytes occurs following estrogen withdrawal (EW) and is associated with impaired focal adhesions (FAs) and a disrupted actin cytoskeleton. RANKL production is mediated by Hedgehog signalling in osteocytes, a signalling pathway associated with the primary cilium, and the ciliary structure is tightly coupled to the cytoskeleton. Therefore, the objective of this study was to investigate the role of the cilium and associated signalling in EW-mediated osteoclastogenic signalling in osteocytes. We report that EW leads to an elongation of the cilium and increase in Hedgehog and osteoclastogenic signalling. Significant trends were identified linking cilia elongation with reductions in cell area and % FA area/cell area, indicating that cilia elongation is associated with disruption of FAs and actin contractility. To verify this, we inhibited FA assembly via αvβ3 antagonism and inhibited actin contractility and demonstrated an elongated cilia and increased expression of Hh markers and Rankl expression. Therefore, our results suggest that the EW conditions associated with osteoporosis lead to a disorganisation of αvβ3 integrins and reduced actin contractility, which were associated with an elongation of the cilium, activation of the Hh pathway and osteoclastogenic paracrine signalling.
PUBLISHED
Keywords: Post-menopausal osteoporosis; RANKL; Integrin; Actin cytoskeleton; Cilium